Relationship Between the Critical Shoulder Angle and Shoulder Disease. Issue 8 (August 2018) - Li, Xinning; Olszewski, Nathan; Abdul-Rassoul, Hussein; Curry, Emily J.; Galvin, Joseph W.; Eichinger, Josef K.
Abstract : In this review, we describe the history of the Critical Shoulder Angle (CSA), the utility of the CSA in identifying rotator cuff tears and glenohumeral osteoarthritis, and the association between the CSA and patient-reported outcomes. Additionally, we address some of the controversies surrounding the CSA with an updated literature review. The CSA is the angle between the plane of the glenoid fossa (the line from the inferior edge of the glenoid to the superior edge of the glenoid) and a line drawn from the inferior edge of the glenoid to the lateral edge of the acromion on a true anteroposterior (Grashey) shoulder radiograph. An increased CSA (>35°) is thought to alter deltoid vectors, which results in increased superior shear forces on the rotator cuff muscles. This increased loading of the rotator cuff may be a risk factor for the development of rotator cuff tears. A decreased CSA (<30°) is associated with glenohumeral arthritis due to the increased compressive forces across the glenohumeral joint. Reports in the literature have both supported and refuted the associations between the CSA, shoulder disease, and clinical treatment outcomes. These conflicting findings may be attributable to the lack of standardized radiographic methods for measuring CSA and/or to measurement errors. Prospective longitudinal cohort studies involving a standard and reproducible method of CSA measurement are needed to elucidate the true relationship between the CSA and shoulder disease.